The Darwinian Legal Model: an Organicist Interpretation of Roscoe Pound’s Early Writings (2020)
Roscoe Pound’s legal organicism is perhaps less well-known than his sociological jurisprudence. In this article, I will trace it back to Pound’ botanical education. I will compare his with classical legal organicism as well as its place in the debate about common-law sources of law. Finally, I will tentatively propose a Darwinian interpretation of the legal organicism in his early writings..